Trends in Non-invasive Prenatal Screening and Invasive Testing in Denmark (2000–2019) and Israel (2011–2019) - Sagi-Dain, Lena; Singer, Amihood; Petersen, Olav B.; Lou, Stina; Vogel, Ida (Frontiers in Medicine, 2021)
Introduction: Following the wide distribution of noninvasive prenatal genetic screening (NIPS), numerous studies have reported a decline in total invasive tests in the recent years, up to 50-70% in some countries. However, in Denmark and Israel we have not experienced these declines. The objective of our study was to evaluate the trends in NIPS and chromosomal microarray analysis (CMA) use in Denmark and Israel. Methods: This retrospective study was performed by data acquisition from the Danish Cytogenetics Central Registry throughout the years 2000-2019, and Israeli Public Health Services, Ministry of Health computerized database (from 2011). Results: Of the 1,243,956 live births registered in Denmark over the years 2000-2019, a relatively steady level of invasive testing around 6% was noted since 2004, as opposed to 13.0% in Israel based on 1,594,962 live births between 2011 to 2019. The average uptake of NIPS was 1.1±0.5% in Denmark vs. 4.3% in Israel (2013-2019). Relatively steady rates of invasive testing were noted in both countries, compared to a slight decline in NIPS in the recent years. Discussion: The recent decrease in the rates of invasive testing in the NIPS era was not observed in Denmark or in Israel. These results imply that Danish and Israeli women and/or health providers might favor the high resolution and yield of CMA testing over the non-invasiveness of NIPS. We explore and discuss this phenomenon, based on five central factors.